Distribution and habitat use of bottlenose dolphin (Tursiops truncatus) in central and south west of Portugal mainland - Almeida, Diana Isabel Faustino (2017)
Tese de mestrado em Biologia da Conservação, apresentada à Universidade de Lisboa, através da Faculdade de Ciências, 2017